2022
DOI: 10.2147/ijgm.s357368
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Prostate Cancer from Prostate with Benign Biopsies: A Predictive and Survival Analysis from Cohort Study

Abstract: Purpose This cohort was to evaluate incidental prostate cancer (iPCa) from men with preoperative benign biopsies and demonstrate their outcomes under different managements. Patients and Methods Between 2015 and 2017, we analyzed the risk factors having iPCa from surgical specimens from men provided with benign preoperative biopsies of their prostates. Furthermore, we compared the survival outcomes according to the different managements after iPCa was diagnosed. Receiver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Predicting malignancy preoperatively by using T-RARP is challenging [20]. Based on our previous works [4,20] and the present one, the application of PSA to predict malignancy in either preoperative benign or no biopsies was robust. Interestingly, we observed different roles of PI-RADS scores in patients with and without preoperative biopsies.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Predicting malignancy preoperatively by using T-RARP is challenging [20]. Based on our previous works [4,20] and the present one, the application of PSA to predict malignancy in either preoperative benign or no biopsies was robust. Interestingly, we observed different roles of PI-RADS scores in patients with and without preoperative biopsies.…”
Section: Discussionmentioning
confidence: 61%
“…In our experience, approximately 19% of men with incidental PCa undergo surgery for benign prostate enlargement, which greatly affects their quality of life [4]. In this cohort, 77% of men with benign preoperative biopsies but considered at a high risk of harboring PCa developed malignancy after T-RARP, and 73% of men considered at a high risk of harboring PCa but without biopsies developed PCa after T-RARP.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…A 10-year retrospective study from Pakistan of 2,386 men aged 25–98 years with a mean age of 68.51 ± 9.22 years reported an incidence rate of about 10.7%, with 90.1% of the patients being T1b, which is remarkably higher than the stage we reported (Janjua et al 2021 ). Among 295 men, 19% had a histopathological report indicating ICP (Yang et al 2022 ). There is inconsistency in the literature with the reported incidence rates of ICP from surgical specimens from men with presumed benign prostate hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, prostate cancer has been diagnosed using a sextant or systematic biopsy (SB), which may miss 20% to 30% of clinically significant prostate cancer (csPC) because of the random sampling approach [ 5 , 6 ]. Recently, Yang et al reported that in 295 men with benign preoperative biopsies undergoing TURP or simple prostatectomy, 57 (19%) were found to have prostate cancer incidentally [ 7 ]. With technical advances in multiparametric magnetic resonance imaging (mpMRI) and promotion by the European Society of Urogenital Radiology and American College of Radiology in the past decades, mpMRI has become an important imaging tool in the diagnostic pathway of prostate cancer [ 8 ].…”
Section: Introductionmentioning
confidence: 99%